(untitled) (ModaPalavra e-periódico, 2019)
The present work relates two areas of Design: Fashion Design and Surface Design, investigating the relationship that is established between the two in the creationand production of clothing. Since in creating fabric prints the designer works in the two-dimensional field and this surface will involve a three-dimensional body when being transformed into clothing, the problems that can be generated from this transformation are discussed, and possible solutions to the question are investigated. For such, a review is made of the subjects involved in the inquiry, reflecting on the themes and the link between the surface and the clothing. Finally, experiments are carried out proposing the virtual prototype as a tool for dialogue between áreas.